Ruralidade no vale do submédio São Francisco: observações a partir da evolução econômica do polo Juazeiro-BA - Petrolina-PE - Neto, José Raimundo Cordeiro; Bezerra Alves, Christiane Luci (Universidade Federal Rural do Rio de Janeiro, 2015)
For decades, the Valley of the São Francisco, in brasilian northeastern, has been objecto of regional development policies. In this article, we discuss the economic evolution this territory showing, the entanglement between "field" and "city", that requiring intervention proposals grounded in the inseparability of these two spaces. Initially, the historical process of local economy consolidation is systematized and problematized basead in various theoretical references. The objective is clarify how were integrated, rural and urban area, around of Polo Juazeiro-Petrolina, through of the productive activity specify rural . The secondary data are used presents the labor market and the spatial distribution of population in the locality. Hence, several numbers clarify the urban-rural relationship, highlighting the agropecuary in local labor market and the concentration of the residents into cities. Thus, the central aspect of rural life presents the establishment of the productive and occupational activity related to rural. The same time, the city has be the main space and organization of social life.